2012
DOI: 10.1002/aenm.201100774
|View full text |Cite
|
Sign up to set email alerts
|

Charge Formation in Pentacene Layers During Solar‐Cell Fabrication: Direct Observation by Electron Spin Resonance

Abstract: Microscopic characterization of charge carriers in solar cells is useful for high-performance cell fabrication because the formation and accumulation of charges in cells greatly affect the device performance. Electron spin resonance (ESR) is suitable for such characterization because it can directly observe charge carriers with spins in these cells. In this work, the ESR method is applied to organic thin-fi lm solar cells to investigate charge formation in such devices. Heterojunction cells of indium tin oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 33 publications
6
71
0
Order By: Relevance
“…The g factor of 2.002 is consistent with that of radical cations (positive polarons) on P3HT in organic field-effect devices [23,24]. The ESR signal of the PEDOT:PSS and the P3HT overlapped with each other because of their similar g factors [19,20].…”
Section: Esr Study Of Devicessupporting
confidence: 60%
See 3 more Smart Citations
“…The g factor of 2.002 is consistent with that of radical cations (positive polarons) on P3HT in organic field-effect devices [23,24]. The ESR signal of the PEDOT:PSS and the P3HT overlapped with each other because of their similar g factors [19,20].…”
Section: Esr Study Of Devicessupporting
confidence: 60%
“…Anion formation decreases J sc and concomitantly decreases V oc [11]. Anion formation should also decrease V oc because of the shift in energy levels at the interfaces [19,20]. The expected decrease in V oc was, indeed, observed (see Fig.…”
Section: Mechanism Of Performance Degradationmentioning
confidence: 65%
See 2 more Smart Citations
“…[9][10][11][12][13][14]16 To fully elucidate the light-soaking phenomenon, electron spin resonance (ESR) spectroscopy is the most suitable technique because ESR is a highly sensitive and nondestructive technique for directly observing the charges in organic semiconductors and their devices at the molecular level. [17][18][19][20][21][22][23][24] ESR studies have demonstrated a clear correlation between performance deterioration and charge accumulation (or trappings) in a normal-type OSC, 18 and have clarified degradation mechanism due to charge formation during device fabrication. 19 As noted above, the light-soaking phenomenon has been considered to be related to charge trappings.…”
mentioning
confidence: 99%